The effect of intellectual capital on Malaysian banks financial performances: Comparative study on conventional and Islamic banks - Navin Kumar, Mahalingam (2016)
In ultra competitive banking industry nowadays, banks could not solely rely on monetary capital for competitive advantage. In this respect, intellectual capital (intangible asset) emerged as viable resources for banks. AFAS (ASEAN Framework Agreement on Services) which will commence in 2020 has put prominence on intellectual capital. This research aims to examine relationship between intellectual capital and financial performances of 32 Malaysian banks (conventional and Islamic) for eight years from 2008 to 2015. In this respect, comparative study between conventional and Islamic banks are undertaken. Value added intellectual coefficient (VAIC) technique is utilised to compute banks’ value added performances. Profitability proxies such as return on asset, return on equity, and data envelopment analysis’ efficiency are used. The banks intellectual capital (human capital, structural capital) and physical capital (capital employed) effect on banks financial performances had been computed by utilisation of panel data estimation method. The results of this research study showed relationships between intellectual capital and banks financial performances between Malaysian conventional and Islamic banks are varied. Moreover, study findings implied intellectual capital is crucial for banks competitive advantage. This study findings can assist banks decision makers and investors in analysing intellectual capital position of Malaysian financial institutions